Pengaruh Profitabilitas terhadap Nilai Perusahaan dengan Kebijakan Hutang sebagai Variabel Moderasi pada Perusahaan Manufaktur di LQ45 Tahun 2023-2025 - Rizza Tiaratu; Anisa Sal Sabilla Putri; Indi Salwa Zahrina; Dwi Batrisya Cahaya; Erika Dwi Maretya Nur Utami; Achmad Miftachul Huda (JURNAL RISET MANAJEMEN (JURMA), 2026)
This study examines how profitability affects company value among manufacturing firms included in the LQ45 index during the 2023–2025 period, with debt policy serving as a moderating variable. Increasing business competition encourages companies to improve their financial performance and market value to attract investors and maintain long-term sustainability. A quantitative research approach with a causal research design was employed to analyze the relationship between the variables. The study used secondary data obtained from audited annual financial statements published on the Indonesia Stock Exchange. Data analysis was conducted using Moderated Regression Analysis (MRA) with the assistance of SPSS version 26. The results indicate that profitability has a significant positive effect on firm value, suggesting that higher profitability enhances investor confidence and contributes to higher market valuations. Furthermore, debt policy significantly moderates the relationship between profitability and firm value by strengthening the influence of profitability. The coefficient of determination increased from below thirteen percent to more than sixty-three percent after including the moderating variable. These findings demonstrate that effective debt management combined with strong profitability contributes to higher firm value and supports sustainable corporate growth and long-term investor confidence.